Process optimisation for pilot-scale production of betamethasone 17-valerate topical products ussing palm olein-based emulsion as drug delivery vehicle - Win, Thazin (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2019)
Palmisone® cream and lotion are topical oil-in-water emulsions of betamethasone 17-valerate which are intended for the treatment of autoimmune skin diseases. These products are unique because the base emulsion was prepared using palm olein which is a major commodity of Malaysia to date. Previous research works proved superior stabilities and efficacies of Palmisone® products when compared to three commercial products in research and development stage. However, data for scale-up studies using palm olein as potential drug delivery vehicle for pharmaceutical products has never been reported. Hence, this study aims to establish and optimise manufacturing process parameters which can produce products with consistent quality for pilot-scale production of Palmisone® products. Initially, lab-scale batches (5 kg per batch) were prepared and the formulation process was repeated three times for both products. The products were formulated using palm olein as oil phase, Span® 20 and Tween® 20 as surfactants, Carbopol® 940 as thickener, chlorocresol as preservative, propylene glycol as solubilizer, betamethasone 17-valerate as active ingredient, honey melon fragrant oil and distilled water as aqueous phase. The products were characterised and subjected to accelerated (6 months) as well as real time stability studies (12 months). Further, the degradation of drug in the products was analysed using HPLC after this assay method was verified as per ICH guidelines. Based on the process knowledge obtained from lab-scale studies, pilot-scale productions of the products were performed using facilities at IKOP Sdn. Bhd. The cream and lotion were scaled-up to minimum (30 kg 3 batches) and maximum (80 kg 3 batches) pilot-scale batches. The products were characterised to establish manufacturing process parameters. The results of lab-scale and pilot-scale formulations were compared and the homogenisation process parameters of 80 kg lots which reproduced products having similar quality as that of lab-scale products were chosen for process optimisation study using Design-Expert ® Software. The optimum homogenisation time and speed were 40 minutes and 3400 rpm. The samples from optimized batch were subjected to stability studies, in vivo efficacy studies, process validation and cleaning validation studies. At the end, the manufacturing process was proven to produce products with consistent quality and stability with process capability indices of approximately 1.3. The knowledge acquired during scale-up process could be valuable for further projects which intend to scale-up formulations using palm olein.